Factors affecting recommendation to use of sharia e-wallet in Indonesia and Malaysia - Fitrianingsih, Eka Rani; Fianto, Bayu Arie (Asian Journal of Islamic Management (AJIM), 2022)
Purpose − This study aims to analyze the effect of variable ease of use, usefulness, perceived risk, and social influence on a recommendation to use sharia e-wallet in Indonesia and Malaysia.Methodology − This study uses a quantitative method. This study uses primary data by conducting a survey through an online questionnaire of 200 respondents with the criteria sharia e-wallet users and living in Indonesia or Malaysia. This research uses the SEM-PLS analysis method.Findings − The results of this study found that variable ease of use, usefulness, and social influence significantly and positively affect the recommendation to use the sharia e-wallet. In contrast, the perceived risk has a negative effect on the recommendation to use a sharia e-wallet. Based on the Multi-Group Analysis (MGA) test, there is no significant difference between Indonesian and Malaysian users for all variables.Originality − This study adds to the literature, especially on the factors influencing recommendation to use in sharia e-wallet. There are limited studies on this topic, especially for sharia e-wallets in Indonesia and Malaysia. The uniqueness of this research is that the primary data used includes respondents in various regions in Indonesia and Malaysia.Practical implications − The results of this study can be used as a reference by the Islamic fintech industry to develop a sharia e-wallet both in terms of product, quality, and others to be better in the future.